Measures to minimize the consumption of public utilities for the maintenance of common property in multiple dwelling units - L. Filimonov, Sergei (2021)
The objective of this research was to develop measures to minimize the consumption of public utilities for the maintenance of common property (CPUCP) in multiple dwelling units. The current housing [1, 6, 8] and civil [2] legislation provides for that consumers of public utilities in multiple dwelling units pay for the consumed resources according to the actual volumes of consumption (if there are individual metering devices) or, if none apply, according to the standards for the consumption of public utilities.